Integrative Model of Culture, Leadership, Trust, and Motivation for Enhancing Performance and HRD in Defense Organizations - Anton Nugroho (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Defense organizations face complex and unpredictable security threats, demanding not only technological advancement but also transformation in human and organizational dimensions.  The purpose of this study is to formulate a conceptual model called the synergic performance enabler model which integrates four strategic variables organizational culture, transformational leadership, institutional trust, and work motivation in improving performance and human resource development in national defense organizations. This study uses a systematic literature review approach, analyzing 40 reputable national and international journal articles indexed in Scopus, SINTA, and Google Scholar between 2015 and 2025. The sources were selected based on relevance to defense sector performance, leadership transformation, organizational behavior, and institutional development. The literature synthesis shows that organizational culture and transformational leadership are consistently associated with increased organizational performance and adaptability, particularly when supported by institutional trust and high intrinsic motivation. These four factors form a mutually reinforcing framework for achieving sustainable defense reform. The proposed synergic performance enabler model addresses gaps in prior research by offering an integrative perspective on human capital management in the defense sector. This study is the first to conceptualize a defense-specific organizational development model that combines leadership, trust, motivation, and culture into a unified strategy.